Optimalisasi Pembelajaran Trigonometri Melalui Kombinasi Geogebra dan Infografis: Pendekatan yang Dinamis dan Menarik - Afifah, Hasna (Jurnal Pendidikan Matematika Undiksha, 2024)
Trigonometry is a branch of mathematics that studies the relationship between angles and sides of triangles. It has many applications in various fields, including physics, engineering, and astronomy.Trigonometry learning is often considered difficult and abstract by students. This is due to several factors, including: the abstract nature of trigonometric concepts and lack of interesting and interactive learning media. One way to overcome this is to use a dynamic and engaging approach. One approach that can be used is to integrate Geogebra and infographics in trigonometry learning. Geogebra is a mathematical software that can be used to create graphs, animations, and simulations. Geogebra can be used to visualize trigonometric concepts dynamically. Infographics are data visualizations that use text, graphs, and images to present information in an engaging and easy-to-understand way. Infographics can be used to explain trigonometric concepts more clearly. Here are some of the benefits of combining Geogebra and infographics in trigonometry learning: improves conceptual understanding, improves problem-solving skills, and increases motivation to learn. A dynamic and engaging approach can make trigonometry learning more interesting and enjoyable. This can help students to be more motivated to learn and understand trigonometric concepts better. Keywords: trigonometry, Geogebra, infographics, dynamic learning, engaging learning